EXPERIMENTAL EVALUATION OF THE SOLID PARTICLES BEHAVIOR IN A VERTICAL AIR FLOW BY USING IMAGING ANALYSIS - EMILIAN-FLORIN MOSNEGUTU; NARCIS BARSAN; ALEXANDRA-DANA CHITIMUS; CLAUDIA TOMOZEI; MIHAIL RISTEA (Journal of Engineering Studies and Research)
To analyse the behavior of a solid particle in a vertical ascending air flow a series of studies have been carried out, both theoretical and experimental. This article presents a new method of imaging analysis of the behavior of a solid particle, in order to extend this study through experimental applications. The working algorithm implies the analysis of images in different positions of the solid particle in the vertical ascending air flow, analysis in relation to a reference image. By using the mathematical apparatus, i.e. Mathcad software, the movement of the solid particle in the air flow has been emphasized.